Race and the Construction of Evidence in Homicide Cases - Pierce, Glenn L. (American journal of criminal justice, 2014)
Research that attempts to document racial or gender disparities in the criminal justice system inevitably paints a distorted picture if only one point in the criminal justice process is examined. For example, studies that look at who is sentenced to death among a group convicted of first-degree murder will miss exposure of biases that occur at earlier stages of the criminal justice process. In this paper, we looked at prosecutorial files on over 400 homicide cases from Caddo Parish, Louisiana (the Shreveport area). Results indicate that even after controlling for aggravating factors, cases with White female victims result in thicker files than other homicides, indicating more prosecutorial effort in attempting to secure convictions in such cases. This, in turn, was related to more severe sentencing of offenders convicted of killing whites and women. On the other hand, cases with black victims resulted in the thinnest case files and the least severe sentences.